Analisis Strategi Digital Content Marketing Dalam Meningkatkan Brand Awareness Dan Omzet Pada Wishyouworeit - Adzkar, M Aqil; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The concept of society 5.0 that has begun to emerge in Japan has become a major topic of social and economic change in the global era. This increasing use of the Internet in Indonesia has led to an increase in social media usage. The number of business operators operating in the same business and offering a variety of similar products or services makes it difficult for the public to decide their choice. The aim of this research is to analyze digital content marketing strategies in improving brand awareness and turnover on wishyouworeit. This research uses descriptive qualitative methods. Data is collected with observation techniques, interviews, and documentation. The informants in this research are the owner or owner wishyouworeit, the marketing wishyouworeit and the consumer wishyuworeit. Research results show that wishyouworeit strategies in content marketing determine objectives, target mapping, content ideas, content creation, content distribution, content amplification, content marketing evaluation, and content marketing improvisation. The strategy applied by wishyouworeit is able to improve brand awareness consumers and can make top of mind on the mind of consumers. Wishyouworeit is also able to increase turnover by 20% to 30% by 2024. Keywords : Digital Content Marketing, Brand Awareness, Wishyouworeit